Software Architecture Superstream Series Architecture Meets Data - Ford, Neal; Richards, Mark; Sadalage, Pramod; Dehghani, Zhamak (O'Reilly Media, Inc., 2021)
With an eye to the future, many organizations have made the move to microservices as a means of decomposing monolithic legacy systems. But what does this move mean for delivering data? Join us to discover how understanding the intersection of software architecture and data can help you achieve new levels of velocity, agility, reliability, and efficiency. If you're looking for ways to manage data as a software architect or developer, these sessions will help you learn what's involved so you can chart a course toward a successful solution. About the Software Architecture Superstream Series: This six-part series of half-day online events focuses on the hottest topics in software architecture, giving you the insights to keep pace with what's next while still accommodating legacy needs. Both seasoned software architects and those looking to break into the field will learn new skills and the latest information on the tools and technologies they need to succeed. What you'll learn-and how you can apply it Explore the intersection of software architecture and data Understand how and when to decompose monolithic data Learn how to apply evolutionary practices to databases and how to apply database refactoring patterns to evolve the database design See what's coming next with data mesh, the next-generation analytical data platform This Superstream is for you because ... You're a developer or architect who wants to understand the intersection of architecture and data. You're currently looking for ways to deliver data to support your businesses goals. You want to become well-versed in the foundations and best practices of software architecture and data. Prerequisites: Come with your questions Have a pen and paper handy to capture notes, insights, and inspiration Recommended follow-up: Read Fundamentals of Software Architecture (book) Read Building Microservices, second edition (book) Read Building Evolutionary Architectures (book) Read Building Event-Driven Microservices (book) Take Software Architecture by Example (live online training course with Mark Richards and Neal Ford) Take Architecture: The Hard Parts (live online training course with Mark Richards and Neal Ford) Take Microservice Fundamentals (live online training course with Sam Newman).